Direct Epoxidation of Propylene over Stabilized Cu+ Surface Sites on Titanium‐Modified Cu2O. Issue 41 (17th July 2015) - Yang, Xiaofang; Kattel, Shyam; Xiong, Ke; Mudiyanselage, Kumudu; Rykov, Sergei; Senanayake, Sanjaya D.; Rodriguez, José A.; Liu, Ping; Stacchiola, Dario J.; Chen, Jingguang G.
Abstract Direct propylene epoxidation by O2 is a challenging reaction because of the strong tendency for complete combustion. Results from the current study demonstrate that by generating highly dispersed and stabilized Cu+ active sites in a TiCuOx mixed oxide the epoxidation selectivity can be tuned. The TiCuOx surface anchors the key surface intermediate, an oxametallacycle, leading to higher selectivity for epoxidation of propylene.